THE FRIENDLINESS OF THE CITY OF HEREDIA WITH THE ELDERS MEASURED FROM THE PHYSICAL CHARACTERISTICS - Alfaro-Sánchez, Marvin (2016)
This research analyzes the measurement of the friendliness level of the city of Heredia regarding elders based on four variables: the quality of neighborhoods -understood as the immediate environment of the elderly, quality and access to green areas in the city, access to different parts of the city using public transportation, and access to a some urban services, each measured throughsimple and combined indicators. The results of the research show that the city of Heredia has a barely acceptable friendliness level -with areas of low and medium-friendliness, due to poor access to green areas, high noise levels, high traffic flows, and some services with poor accessibility.